Human genetic variation and therapeutic development - John, Sally; Davies, Nick (Henry Stewart Talks, 2007)
Common variation within the human genome, The drug discovery pipeline, The contribution of genetic variation to target identification, validation and clinical development, Defining drug targets, Genotype phenotype correlation, The druggable genome, Clinical trials, Whole genome by association methods, Functional relevance of genetic variation, Implications for treatments
Archived at 2018/05/31